2020
DOI: 10.1002/srin.202000262
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Operational Parameters on Particle Movement and Distribution at the Top of a Bell‐Less Blast Furnace Based on Discrete Element Method

Abstract: In blast furnaces, the chute is the key device determining burden distribution. The effects of the chute's geometric and operational parameters on burden distribution have seldom been studied. Herein, the top of a bell‐less blast furnace is modeled based on the discrete element method to investigate the effects of chute length, stock‐line level and chute angle on particle movement, and radial burden distribution. The results indicate that burden particles are more likely to slide toward the opposite to the rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The interplay of these forces determines the bulk behavior of the flow in the chute, specifically how compact/dilute the flow is at the chute outlet. When it comes to point (2), researchers have researchers have studied the effect of chute design [45] and operation [46,47] on the stream width and thickness, and how these factors affect segregation during layer build-up. These aspects are discussed later, in Section 2.3.…”
Section: • During Flow Through the Charging Apparatusmentioning
confidence: 99%
See 3 more Smart Citations
“…The interplay of these forces determines the bulk behavior of the flow in the chute, specifically how compact/dilute the flow is at the chute outlet. When it comes to point (2), researchers have researchers have studied the effect of chute design [45] and operation [46,47] on the stream width and thickness, and how these factors affect segregation during layer build-up. These aspects are discussed later, in Section 2.3.…”
Section: • During Flow Through the Charging Apparatusmentioning
confidence: 99%
“…As the tilting angle and length increase, the particles' residence time on the chute becomes longer and therefore, the particles experience centrifugal and Coriolis forces for longer times. Consequently, the material stream will tend to move along one side of the chute and, according to Hong et al [47], this tendency increases with the chute angle and length. Fig.…”
Section: Rotating Chutementioning
confidence: 99%
See 2 more Smart Citations
“…They compared the experimental results with numerical results from DEM, the results showed that the particle simulation of the charging process is highly reliable for predicting the particle trajectories in the BF. Hong et al [14] established a 1:1 DEM model to investigate the effects of chute length, stock-line level, and chute angle on the movement of particles and their radial distribution.…”
Section: Introductionmentioning
confidence: 99%